Limited Asset Market Participation: Does it Really Matter for Monetary Policy? - Guido Ascari; Andrea Colciago; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
We study the design of monetary policy in an economy characterized by staggered wage and price contracts together with limited asset market participation (LAMP). Contrary to previous results, we find that once nominal wage stickiness, an incontrovertible empirical fact, is considered: i) the Taylor Principle is restored as a necessary condition for equilibrium determinacy for any empirically plausible degree of LAMP; ii) the effect of LAMP for the design of optimal monetary policy are minor; iii) optimal interest rate rules become active no matter the degree of asset market participation. For this reasons we argue that LAMP does not matter much for monetary policy.
Keywords: E50; E52; 330; optimal monetary policy; sticky wages; non-Ricardian household; determinacy; optimal simple rules